2020
DOI: 10.3390/rs12050866
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Machine Learning Optimized by The Genetic Algorithm in Ionospheric Models Using Long-Term Multi-Instrument Observations

Abstract: The ionospheric delay is of paramount importance to radio communication, satellite navigation and positioning. It is necessary to predict high-accuracy ionospheric peak parameters for single frequency receivers. In this study, the state-of-the-art artificial neural network (ANN) technique optimized by the genetic algorithm is used to develop global ionospheric models for predicting foF2 and hmF2. The models are based on long-term multiple measurements including ionospheric peak frequency model (GIPFM) and glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…In addition, these models successfully capture the prominent large-scale ionospheric phenomena, such as the diurnal and seasonal variations of equatorial ionization anomaly, ionospheric annual anomaly (Rishbeth et al, 2000), and the ionospheric trough. The powerful performance of ANN models has also been verified in Li et al's study (Li et al, 2020), the accuracies of foF2 and hmF2 models built by ANN technique were 20-30% higher than the International Reference Ionosphere (IRI) model, and the ANN models present a good capability to reproduce the global or regional ionospheric spatial-temporal characteristics. The above literatures demonstrate that the ANN technique could successfully extract the multivariable nonlinear relationship between ionospheric parameters and geographic location, solar-geomagnetic indices, thermospheric winds, etc.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, these models successfully capture the prominent large-scale ionospheric phenomena, such as the diurnal and seasonal variations of equatorial ionization anomaly, ionospheric annual anomaly (Rishbeth et al, 2000), and the ionospheric trough. The powerful performance of ANN models has also been verified in Li et al's study (Li et al, 2020), the accuracies of foF2 and hmF2 models built by ANN technique were 20-30% higher than the International Reference Ionosphere (IRI) model, and the ANN models present a good capability to reproduce the global or regional ionospheric spatial-temporal characteristics. The above literatures demonstrate that the ANN technique could successfully extract the multivariable nonlinear relationship between ionospheric parameters and geographic location, solar-geomagnetic indices, thermospheric winds, etc.…”
Section: Introductionmentioning
confidence: 67%
“…For more details about the activation functions, the readers are referred to Specht's study (Specht, 1990). Hundreds of experiments indicated that the mean square error (MSE) of the neural network was minimized when the neurons in three hidden layers were 16, 14 and 12, respectively (Li et al, 2020). In this study, both COSMIC's profiles and ionosonde's observations were utilized to build global ionospheric models for predicting foF2 and hmF2 based on the neural network's architecture, respectively.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…This study is a further extension of the ANN algorithm proposed by Li, Zhao, He, et al., (2020). Based on the success of the ANN model in predicting ionospheric peak parameters foF2 and hmF2, this study uses the profiles obtained from multiple RO systems (COSMIC‐1, FY‐3C) and the observations of global Digisondes to develop a completely global three‐dimensional electron density model with an artificial neural network, namely ANN‐TDD.…”
Section: Discussionmentioning
confidence: 95%
“…This study is a further extension of the ANN algorithm proposed by [Li et al, 2020b]. Based on the success of the ANN model in predicting ionospheric peak…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation